The English Services I & II - Byrd, William 1539/40-1623; Monson, Craig A.; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1980)
Vol. 1: Byrd’s music for the Anglican service remains one of the least appreciated areas of his output. Its manner is generally restrained; its sources, for the most part, are problematical. Abjuring word painting and imitation, settings of the Preces and Responses, Psalms, Service and Litany rely on harmonic variety for their musical interest and continuity.
Vol. 2: Since The Great Service was rediscovered in manuscripts at Durham, it has come to be recognised not only as Byrd’s most important work for the Anglican church, but also as one of the masterpieces of Elizabethan art. In the hope of recapturing the composer’s intentions as nearly as possible, the present edition follows the scoring of pre-Restoration sources more precisely than did either Fellowes or Tudor Church Music, and restores the parts that have subsequently come to light.
edited from manuscript and printed sources
Keywords: Church music; Vocal music; Psalm; Organ; United Kingdom